Reverse Epidemiology: An Experimental Framework to Drive Leishmania Biomarker Discovery in situ by Functional Genetic Screening Using Relevant Animal Models - Piel, Laura; Pescher, Pascale; Späth, Gerald F. (Frontiers in Cellular and Infection Microbiology, 2018)
Leishmania biomarker discovery remains an important challenge that needs to be revisited in light of our increasing knowledge on parasite-specific biology, notably its genome instability. In the absence of classical transcriptional regulation in these early-branching eukaryotes, fluctuations in transcript abundance can be generated by gene and chromosome amplifications, which have been linked to parasite phenotypic variability with respect to virulence, tissue tropism, and drug resistance. Conducting in vitro evolutionary experiments to study mechanisms of Leishmania environmental adaptation, we recently validated the link between parasite genetic amplification and fitness gain, thus defining gene and chromosome copy number variations as important Leishmania biomarkers. These experiments also demonstrated that long-term Leishmania culture adaptation can strongly interfere with epidemiologically relevant, genetic signals, which challenges current protocols for biomarker discovery, all of which rely on in vitro expansion of clinical isolates. Here we propose a long-term culture-independent experimental framework termed ‘reverse‘ epidemiology, which applies established protocols of functional genetic screens of cosmid transfected parasites in relevant animal models for the identification of genetic loci that then inform targeted clinical studies for their validation as Leishmania biomarkers.